ANALISIS KINERJA APARAT PEMERINTAH DAERAH (Studi Empiris Pada Pemerintah Kabupaten Bengkalis) - Endang Sri Wahyuni; Rosmida Rosmida (Inovbiz: Jurnal Inovasi Bisnis, 2016)
Abstract: This purpose of this study is to examine the effect of organizational culture and locus of control, on the performance of district governments. The population in this study are all of working units Bengkalis District Government and purposive sampling is used as sampling method. This study uses questioner for 183 respondents. The analysis technique used is the technique of  path analysis   using  SPSS  version  17.0.  The results showed  prove that  organi- zational culture affect on the performance of district governments, and locus of control affect on the performance of district governments. Keywords: Performance, Organizational, culture, Locus Of Control (LOC), district, governments.